Water safety plans by utilities: a review of research on implementation - Roeger, Alexandra (2018)
Water supply is essential to public health, quality of life, environmental protection, economic activity, and sustainable development. In this context, it is imperative to assure the continuous improvement of all processes and practices conducive to guarantee water quality and safety. Water Safety Plans (WSPs) by water utilities are an important public policy tool to accomplish these goals. This manuscript reviews the international evidence of the adoption and implementation of water safety planning and reports the current situation in Portugal, as part of the necessary adjustment of the national legal framework to the publication of the Directive (EU) 2015/1787, October 6th, on water quality for human consumption. The aim is to draw lessons from several successful WSP experiments around the world and extract lessons from these cases when drafting new legislation in Portugal and elsewhere. Findings suggest there are four critical dimensions and key elements of success in developing and implementing WSPs: leadership commitment, technical knowledge, governance, and interagency collaboration.